Exploring potential phytocompounds from black cumin as drug molecules against SARS-CoV-2 infections through bioinformatics analysis - Md. Ahad Ali; Humaira Sheikh; Md. Selim Reza; Tripti Rani Paul; Tasfia Noor; Neeraj Kumar; Mashooq Ahmad Bhat; Md. Nurul Haque Mollah (PLoS ONE, 2026)
SARS-CoV-2 was identified at the end of 2019 as the key cause of COVID-19, a global pandemic. As remedies, different vaccines as well as synthetic drugs have been recommended. However, the availability of natural drugs against SARS-CoV-2 infection is limited, although natural drugs are considered as less toxic than synthetic drugs, and vaccine efficacy is gradually weakened due to unstable RNA sequence patterns of SARS-CoV-2. Black-cumin is a well-known medicinal plant, but it was not rigorously investigated against SARS-CoV-2 infections. This study attempted to investigate this issue, rigorously. In order to explore effective bioactive phytocompounds from black-cumin (BC) through bioinformatics analysis, we selected top-ranked 11 drug target proteins/receptors of which five receptors were SARS-CoV-2 proteins/proteases (S, N, RdRp, 3CLpro, PLpro) and the other six receptors were host proteins (ACE2, MAPK8, TMPRSS2, IL6, TNF, and NFKBIA) associated with the infection by the systematic literature review. We computed binding affinity scores (BAS) for each phytochemical of BC with each of those 11 receptors. Top-ranked five phytocompounds (Silibinin, Taraxerol, Beta amyrin, Cycloartenol, and Alpha-sitosterol) were selected based on their highest average BAS across our proposed receptor, these phytocompounds also showed better binding capabilities against the other independent receptors. Then we selected top-ranked three complexes (ACE2 vs. silibinin, Spike vs. beta amyrin, and MAPK8 vs. Taraxerol) to investigate their binding stability using dynamic simulation (i.e., RMSD, RMSF, DCCM, PCA, and FEL) and MM-GBSA studies and found their stable performance. The ADMET, Bioactivity, and DFT analysis results supported the drug-likeness properties of the proposed phytocompounds. Therefore, the findings of this article might be useful resources for taking an alternative treatment plan against SARS-CoV-2 infections.